Agroforestry Research in India - Issues and Strategies - Singh, G.B. (Indian Journal of Agroforestry, 2020)
To improve productivity of agricultural lands in the near future, new approaches in farming systems will be required. The future agricultural technologies must assure sustainability by optimising productivity. Adaption of agroforestry on all kinds of wastelands in the country and incorporation of multipurpose trees in the already practiced farming/ cropping systems seems an option of great promise to achieve this objective. After the establishment of the All India Coordinated Research Project on Agroforestry in 1983 and the National Research Centre for Agroforestry at Jhansi in 1988, systematic research efforts on agroforestry have been made in different agro-climatic zones of the country. This paper reviews the outcome of these research efforts in general and issues and strategies to be adapted for the agroforestry research and extension in the future in particular. The topics covered are: (i) research achievements in agroforestry and their impact on production and productivity, (ii) issues and strategies for proper planning and (iii) thrust areas for future research.